Трансформація цінностей освіти в інформаційному суспільстві - Резнік, Світлана Миколаївна (НТУ "ХПІ", 2015)
The value of education, including higher education – is quite important. In our country, traditionally large volume of enrolment in General secondary education of the population. A significant number of high school graduates continuing to study at higher education institutions. On the one hand, we see a trend of education are presented. On the other hand, concerns the quality of knowledge and level of General education of citizens. Therefore, in today's society for some part of the population education and learning is significant, important value. But for another – these values are not linked: trying to get a higher education, they do not always want to work harder on difficult tasks, the maximum deepening of knowledge. Researchers analyzing modern society and trends of its development noted that the information revolution of today does not contribute to snanny, and, conversely, prevent it. That is an increase in information does not increase knowledge. In the conditions of information society the attention the teachers should guide the students awareness of the value of knowledge, a deep understanding of information and intelligence. The article emphasizes the importance of humanitarian training of future engineers. Special attention should be paid to the values of the Humanities that develops social and communicative competence of the student, critical thinking and contributes to the establishment of humanistic principles in society and in the life of every person.
Transformation of values education in the information society
Keywords: освіта України; ВНЗ; формування цінностей; вчені; понятійне мислення; загальна освіченість; values; higher education; information society; knowledge; information; human training